Etiological profile of bovine mastitis from dairy farms in the Western Paraná, Brazil - Jardim, Júlia Gazzoni (2014)
The aim of this study was evaluate the occurrence, infectious etiology and risk factors associated with mastitis in 331 dairy cows from sixteen farms located in the region of Marechal Cândido Rondon in the State of Paraná, Brazil. Both cows as the properties were selected of a non-random form and being selected 20% of lactation cows from each farm. The test for identification of subclinical mastitis was the California Mastitis Test and the diagnosis of the clinical mastitis was carried out by the observation of signs of inflammation in the udder and macroscopic changes in milk. Of lactating cows, 195 (60.77%) were positive for mastitis and 93,75% of the farms analyzed had at least one positive animal. The etiologic agents isolated in a total of three hundred twenty-nine samples were Staphylococcus aureus (47.2%), Staphylococcus sp. (29.2%), Streptococcus dysgalactiae (18.1%), Streptococcus uberis (16,7%), Corynebaterium spp. (11,1%) and Streptococcus intermedius (1.39%). Besides, was evaluated the interaction of the type of mechanical milking in function of the mastitis degree and the use of the disinfection of teats before and after milking was not interference in mastitis incidence, however, the accomplishment of the disinfection of teats before and after -dipping favored in the control of subclinical mastitis. We conclude that the significant occurrence of mastitis in herds is due to improper management conditions. The adoption of good management and prophylactic measures, assisted by a professional of Animal Science surgeon will allow the reduction of this disease in herds.